Good natured the origins of right and wrong in humans and other animals - Waal, Frans B. M. de 1948-2024 (Harvard Univ. Press, 1996)
Waal shows how ethical behavior is as much a matter of evolution as any other trait.
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Comportamento social animal; Comportement humain; Comportement social des animaux; Etologia animal; Evolucao humana; Gedrag; Goed en kwaad; Morale évolutionniste; Primaten; Animal behavior; Ethics; Ethics, Evolutionary; Human behavior; Verhaltensforschung; Verhaltenspsychologie; Evolutionäre Ethik